PELATIHAN PEMBUATAN DIGITAL LOOKBOOK BERBASIS AI BAGI MASYARAKAT DI LKP AZ ZIKRA - Hermawan, Rudi; Wijaya, Rian Farta; Budianto, Eko; Septian, Muhammad; As'ary, Muhammad Hasyim; Sitepu, Andri Ismail (Smart Education, 2025)
Abstract: The rapid development of artificial intelligence (AI) technology presents both challenges and opportunities for the general public, particularly in the creative economy sector. This community service activity aims to improve the digital literacy and creative competency of the community at LKP Az Zikra through training on creating digital lookbooks using AI-based platforms. The method employed involves direct training with a